Exploration of Healthcare Sensitive Systems and Services for Supporting Ambient Assisted Living of Diversified Social Groups in South Korea - Chang, Seongju; Nam, Hyunjae (European Journal of Sustainable Development, 2023)
Different social groups normally have specific sets of requirements and priorities in relation to their surrounding living environment. In our research, we conducted an extensive survey on the preferred conditions and demands for four different domains of daily life: healthcare, environment, activity, and information. Carefully composed sets of questionnaires were distributed to 800 people representing diversified social groups in South Korea classified by gender, age, occupation, co-residents, home location, housing style, economic level, and chronic disease. Their responses were collected and analyzed through cross-tabulation to identify characteristic preference patterns concerning their immediate housing unit, residential cluster, and close neighborhood environment and services. Based on the extracted socio-environmental preferences of the different social groups in South Korea, we developed a web-based information system called AALPSS (Ambient Assisted Living Pattern Support System), which includes a total of 100 selected healthcare-sensitive system/service patterns to support the optimum design and operation of artifacts and facilitate the promotion of a healthy silver life. Each pattern is organized based on Christopher Alexander's 'Pattern Language' format and can be browsed and rated by different online users with diverse social profiles. This information system, therefore, has the potential to evolve into a better-tuned healthcare-related system/service decision support system, enhancing social sustainability within a community. Keywords: social group, ambient assisted living, preferred life pattern, healthcare sensitive environment, online information system